2023
DOI: 10.1039/d3ra00750b
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal of phloretin with isoniazid: preparation, characterization, and evaluation

Abstract: Phloretin and isoniazid formed new cocrystal and the structure, solubility and antitumor activities were study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The solubility and dissolution rate of solid drugs were changed due to the formation of cocrystals, which affected the release and absorption of drugs in vivo. The solubility results of pure Phl were selected from the last experimental data . According to the powder dissolution curve of the Phl–4B cocrystal (Figure ), the cocrystal reached equilibrium solubility (49.93 ± 9.69 μg·mL –1 , P > 0.05) in pH 1.2 buffer for 540–1440 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The solubility and dissolution rate of solid drugs were changed due to the formation of cocrystals, which affected the release and absorption of drugs in vivo. The solubility results of pure Phl were selected from the last experimental data . According to the powder dissolution curve of the Phl–4B cocrystal (Figure ), the cocrystal reached equilibrium solubility (49.93 ± 9.69 μg·mL –1 , P > 0.05) in pH 1.2 buffer for 540–1440 min.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro simulated digestion experiments of Phl and Phl–4B cocrystal were performed in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF). The release rule of pure Phl was selected from the last experimental data . According to Figure , the release rates of Phl and Phl–4B cocrystal at 120 min were 10.78% and 15.18%, respectively, during the incubation stage of gastric digestion, and the Phl–4B cocrystal release rate was significantly higher than that of the Phl raw material at this stage ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B, within the range of experimental concentration trilobatin showed the same strong ABTS free radical scavenging ability as Vc. Previous research showed that phloretin also had significant DPPH and ABTS radical scavenging activities (Lu et al, 2023). The similar effects of trilobatin and phloretin on DPPH and ABTS free radicals might be due to their similar structures.…”
Section: Effects Of Trilobatin On Antioxidant Activitiesmentioning
confidence: 93%